achatina fulica: parasitology test´s of specimens collected in the san miguel urbanization (mérida) (Revista Venezolana de Salud Pública, 2018)
We present the findings in feces and pedal mucus from parasitological study on specimens collected of A. fulica in San Miguel II community, Merida. Was negative the pedal mucus, and was found in feces 70.6% of parasite rate, detected the taxa Entamoeba, Giardia, Endolimax, Toxocara, Trichuris and Hymenolepis, well as larval stage of order Strongylida, additional evolutionary stages of Blastocystis sp.
Keywords: Achatina fulica; African snail; parasites; diagnosis